Intracompartmental pressure testing: results of an international survey of current clinical practice, highlighting the need for standardised protocols. Issue 12 (7th September 2011) - Hislop, Matthew; Tierney, Paul
Abstract : Despite more recent non-invasive modalities generating some credence in the literature, intracompartmental pressure testing is still considered the 'gold standard' for investigating chronic exertional compartment syndrome (CECS). Intracompartmental pressure testing, when used correctly, has been shown to be accurate and reliable. However, it is a user-dependent investigation, and the manner in which the investigation is conducted plays a large role in the outcome of the test. Despite this, a standard, reproducible protocol for intracompartmental pressure testing has not been described. This results in confusion regarding interpretation of results and reduces the tests' reliability. A summary of the current understanding of CECS is presented, along with the results of a survey of specialists in Australia and New Zealand who perform intracompartmental pressure testing, which confirms that a uniform approach is currently not used in clinical practice. This highlights the need for a consensus and standardised approach to intracompartmental pressure testing.